Microsoft SQL Server 2012 T-SQL - Tom Coffing, Debra Aaron (Tera-Tom genius series, 2015)
One of the most popular databases worldwide is the Microsoft's SQL Server. The Microsoft Azure Cloud is rapidly making T-SQL one of the standards of SQL among millions of companies. The Microsoft SQL Server 2012 T-SQL book is your key to mastering T-SQL. With easy to use sample tables, and 700 pages of real-world example's and explanations, this book is your perfect reference guide. Each chapter in this book starts with simple examples and continues to use a building block approach to teach both the new user and the advanced user. Pleasing to the eye, and stimulating to the mind, makes this book a worldwide masterpiece where all can learn.